Peran Kesulitan Regulasi Emosi Dalam Memediasi Pola Asuh Otoriter Ibu Dengan Intensi Menyakiti Diri Pada Remaja - Rini Setyowati; Nabila Fairuzindra (Universitas Muhammadiyah Jember, 2023)
This study aims to determine the role of emotional regulation difficulties in mediating maternal authoritarian parenting and self-harm intentions in adolescents. All students of SMA Batik 1 Surakarta are the population of this study. The sample used is 264 students, taken using a proportionate stratified random sampling technique. Data collection used a scale consisting of the self-harm intention scale (α = 0.917), the maternal authoritarian parenting style scale (α = 0.882), and the Difficulties in Emotion Regulation Scale/DERS scale (α = 0.913). The results of the mediation analysis showed that there was a significant relationship between the mother's authoritarian parenting and the self-harm intentions through difficulty in regulating emotions in adolescents (p 0.001). The mediating role of emotional regulation difficulties on the relationship between maternal authoritarian parenting and self-harm intentions in adolescents is partial/incomplete and the estimated direct effect between maternal authoritarian parenting and self-harm is greater than the mediating effect of emotional regulation difficulties (0.005 0.043). This is possible because there are other factors that are more influential as a mediator between the maternal authoritarian parenting and the self-harm intentions than the difficulty of emotional regulation.